PARTISIPASI MASYARAKAT DALAM MENGURANGI RISIKO BENCANA BANJIR DI KECAMATAN DEPATI TUJUH KABUPATEN KERINCI - Agung Putra Rizki (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
ABSTRACTThis research aims to. knowing the level of community participation in reducing risk. flood disasters such as when the rainy season will come or pre-flood disasters in Depati Tujuh District. Kerinci. The type of research approach in this thesis uses a quantitative research approach. Data collection techniques in this study are using questionnaires and document studies. The informants involved in this research are 10 heads of families. of the 4 villages that researchers consider to be the worst affected by the flood, namely Koto Lanang Village, Ladeh Village, Baru Kubang Hamlet and Lubuk Suli Village. So the total sample is 40 households. The results of the study. From this it can be seen that the level of community participation in reducing disaster risk. Floods in Depati Tujuh Subdistrict, Kerinci Regency, are high, namely 85% of the total respondents and the form of citizen participation in this. reduce the risk of flooding in Depati District. The seven districts of Kerinci are managing waste disposal, cleaning drainage channels, repairing forts or embankments and. plant Trees.